2018
DOI: 10.1056/nejmc1806941
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis in Norovirus in Response to Favipiravir Treatment

Abstract: Some changes to the conditions for approval were decided in the course of the deliberation. The revised conditions for approval are as follows:[Conditions for approval] 1. The applicant is required to conduct a pharmacokinetic study in accordance with the approved dosage and administration in Japan, and submit the study data and analysis results immediately after the completion of the study and within 1 year after the date of the marketing approval.2. The applicant is required to conduct a clinical study of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 5 publications
(2 reference statements)
1
40
0
Order By: Relevance
“…The antiviral 6-fluoro-3-hydroxy-2-pyrazinecarboxamide (T-705, favipiravir) Favipavir (FP) is a RNA-dependent RNA polymerase (RdRp) inhibitor. Its use was approved only in Japan for the treatment of influenza infection and it is distributed only upon request by the Minister of Health, Labor and Welfare of Japan to avoid irrational prescriptions [50] In addition to its anti-influenza activity, FP blocks the replication of other RNA viruses [51]. FP has been used for the treatment of human infection with life-threatening Ebola virus and severe fever with thrombocytopenia syndrome [52].…”
Section: Favipavirmentioning
confidence: 99%
“…The antiviral 6-fluoro-3-hydroxy-2-pyrazinecarboxamide (T-705, favipiravir) Favipavir (FP) is a RNA-dependent RNA polymerase (RdRp) inhibitor. Its use was approved only in Japan for the treatment of influenza infection and it is distributed only upon request by the Minister of Health, Labor and Welfare of Japan to avoid irrational prescriptions [50] In addition to its anti-influenza activity, FP blocks the replication of other RNA viruses [51]. FP has been used for the treatment of human infection with life-threatening Ebola virus and severe fever with thrombocytopenia syndrome [52].…”
Section: Favipavirmentioning
confidence: 99%
“…Prolonged shedding times of norovirus have been reported by several studies in both symptomatic and apparently asymptomatic individuals with CVID. Shedding times have been reported by others as long as 1200 days with serial positive faecal samples and gastrointestinal biopsies, while we have recently described a patient infected with the US95/96 strain of norovirus (which circulated until 2002) who was still excreting virus in 2017 . Of particular interest in this regard is the potential association of norovirus with “CVID enteropathy.” This term has been used to describe various pathological entities in CVID patients with diarrhoea, including nonspecific colitis or inflammation resembling classical inflammatory bowel disease.…”
Section: Norovirusmentioning
confidence: 71%
“…Paradoxically, other groups have reported clinical response to anti‐TNF therapies and steroids, although histological response to these therapies has not been documented . Recently, we have treated a patient with the novel antiviral favipiravir and observed marked changes in the dominant viral haplotype as well as accelerated mutagenesis in minority variants, coinciding with clinical response . Another potential treatment under evaluation is nitazoxanide, currently being formally evaluated in post‐stem cell transplant patients in the United States .…”
Section: Norovirusmentioning
confidence: 99%
“…Despite their wide clinical application, the potential side effects or unintended off-target effects of nucleoside analogues should be considered. Induction of mutagenesis by T705 treatment in patients has raised questions for treating chronic norovirus infections [18]. Previous studies have reported that 2'-FdC exhibits delayed toxicity after prolonged exposure, and no adverse clinical effects were observed in rats and woodchucks after 90 days of treatment [20].…”
Section: Resultsmentioning
confidence: 99%
“…Favipiravir, also known as T-705, has been approved for the treatment of influenza in Japan and has been repositioned to treat patients with Ebola virus infection [16,17]. It has been shown to be effective against noroviruses, but the treatment can induce mutagenesis in mice and in patients, challenging the application of favipiravir for treating chronic norovirus infection [18].…”
Section: Introductionmentioning
confidence: 99%